Being Christian, being Australian contemporary Christianity down under - Lawton, William; Moore Theological College (Homebush West, NSW Lancer, 1988)
Includes bibliographical references.
Possibly a second copy......NOS 26/1/04.
Keywords: Christian life -- Australia